25 Years of ‘The Himalayan Geographers’: Reflection in Geography Research - Poudel, Krishna Prasad (The Himalayan Geographers, 2025)
This article has covered the summary and also the annotated bibliography of the articles published in the journal of ‘The Himalayan Geographers’ between 2001 and 2024 with a purpose to analyze reflection in geography research in the country. Specifically study has envisioned on distribution of key field of thematic areas, geographical coverage of case studies, theoretical, methodological and technological concerns of the researchers, regularity of faculty’s involvements, working culture in multi and interdisciplinary and joint authorships in publications. At first, scanned all the articles from entire volumes published. Keywords of the title of each article were traced. Based on those keywords thematic area/s were listed. Location of study area or geographic coverage and field and author/s of each article were compiled and prepared a summary table. Findings were: each volume of journal contained at least 6 in minimum to 13 in maximum; eight different thematic fields of the content, at least 6 in agriculture and related field to 21 in settlements and social issues of article were identified; most of the articles applied new techniques, specifically on the study of land use land cover change; primary survey and field based information; studies largely confined in Pokhara and its vicinities; only two articles were taken case beyond the national border. Interdisciplinary and joint authorship cultures in writing articles are still needed to improve. Only a few numbers of authors had written couple of articles. Diversification among the authors and interdisciplinary and multi authorship culture are recommended. Regularity of journal and increasing visibility are also points to be followed in the future.